Miguela’s papers - Niño, Jairo Anibal (Rastros Rostros, 2002)
I was about to finish my first year of medical school when I met Miguela. That day my spirits were broken because I had not done well on an anatomy exam. A torrential rain was pouring down, taking up half of the hospital. The other half was illuminated by a shining sun as if the rain had stopped in front of the light door without daring to enter. Under different circumstances, this very special phenomenon would have astonished me with the same intensity as that experienced by a child running with difficulty down the stairs, landing in a courtyard and, leaning on his crutches, placing his hand either in the water or in the sun.